O estágio supervisionado na Educação Especial, como componente curricular da formação do Pedagogo - CARVALHO, Heloisa Helena Ferreira de (2023)
This research was built from the curricular component of supervised internship in Special Needs Education, completed by students of the pedagogy course at the Federal University of Pará, Campus Altamira. Aiming to understand the impacts of the internship on the students' academic life, their perceptions about their education, skills and abilities and their feelings of security or not, about the work activity experienced during the internship. The methodology used was a qualitative approach, through bibliographic and documentary research, linked to participant observation and interviews. As a result, based on the analysis of the interviewees' responses, the internship was relevant to their professional training, enabling them to make correspondences between theory and practice. However, they reported that they still do not feel qualified to work in Special Needs Education, because they do not identify with the modality and/or because they feel the need for improvement.